The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5222/head.2017.204
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence, Depression and Anxiety During Pregnancy

Abstract: Giriş: Bu çalışma, gebeler arasında aile içi şiddet sıklığının saptanması, ilişkili olduğu düşünülen bazı değişkenlerin incelenmesi, depresyon ve kaygı düzeylerinin değerlendirilmesi amacı ile yapılmıştır. Yöntem: Çalışma, 15 Ocak-15 Temmuz 2013 tarihleri arasında Sakarya ili Eğitim ve Araştırma Hastanesinin kadın doğum polikliniğine başvuran gebe kadınlar üzerinde gerçekleştirilen kesitsel tipte bir araştırmadır. Çalışma süresince hastanenin kadın doğum polikliniğine başvuran ve çalışmaya katılmayı kabul eden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
11
1
3
Order By: Relevance
“…Furthermore, a history of child abuse was related to higher depression among women, consistently with other ndings (79)(80)(81)(82). Hence, the loss of attachment and the absence of a secure life were the main features for women to experience depression (83,84).…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, a history of child abuse was related to higher depression among women, consistently with other ndings (79)(80)(81)(82). Hence, the loss of attachment and the absence of a secure life were the main features for women to experience depression (83,84).…”
Section: Discussionsupporting
confidence: 77%
“…The studies reporting the effects of violence on women are also limited. Seven studies reported the consequences related to the pregnancy process in women subjected to violence (hemorrhage, pain, abortion, premature birth) 18,19,21,23–27,30 . Furthermore, there were five studies mentioning psychological results (decrease in self‐esteem, the fear of partner, concealing violence, not showing the infant to the partner), and two studies 19,25 mentioning physical complaints (nosebleeding, foot break, tooth break, bruises on the body).…”
Section: Resultsmentioning
confidence: 99%
“…Cultural differences are also another parameter that should be taken into account in changes in prevalence. The fact that the two studies mentioned were carried out in different cultural structures of Turkey may help us understand changes in prevalence (Cengiz et al, 2014 29 —in the west of TR, the prevalence of IPVP was 2.37%; Nur, 2014 30 —in the Central Anatolia Region of TR, the prevalence of IPVP was 37.9%). The time of examining violence may also be another confounding reason which led to differences in prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…suz etkileyen önemli bir sağlık problemidir. 15 Dünyada her dört kadından biri gebeliğinde fiziksel ya da cinsel olarak genellikle eşi/partneri tarafından istismar edilmektedir. 16 Bu araştırmada "Aile içi şiddete ait özellikler" alt boyut puan ortalamasının 3,97±0,6 olduğu belirlenmiştir.…”
Section: Discussionunclassified